Socio-Economic Determinants of Farmers’ Adoption of Rotational Woodlot Technology in Kigorobya Sub-County, Hoima District, Uganda - Buyinza, M.; Banana, A. Y.; G., Nabanoga; Ntakimye, A. (South African Journal of Agricultural Extension, 2008)
Understanding the factors affecting farmers’ adoption of rotational woodlot technologies is critical to the success of implementing tree planting programmes. This paper evaluates, using logistic and multiple regression analyses, the socioeconomic factors that influence farmers’ decisions to adopt rotational woodlot technology in the farming systems of Uganda, based on a survey of 120 farmers in Kigorobya subcounty, Hoima district. The analyses demonstrate that farmers make decisions about woodlot technology based on household and field characteristics. The factors that significantly influenced adoption decisions included: gender, tree tenure security, seed supply, contact with extension and research agencies, soil erosion index, size of landholding, fuelwood scarcity, and main source of family income. To promote greater adoption of rotational woodlot technology, particular attention should be placed on the use of appropriate socioeconomic characterization, to better target technologies to areas with greater adoption potential.
Keywords: Rotational woodlot; Adoption; Logit model; Uganda